Comparison of biochemical and anthropometric parameters in complicated and uncomplicated severe acute malnutrition among children aged 6 to 59 months: a cross-sectional study - Malvika Mishra; Prashant Tripathi; Pratibha Singh; Yashwant Kumar Rao; Desh Deepak Singh (Open Exploration Publishing Inc., 2023)
Aim: The frequency of severe acute malnutrition (SAM) is the highest in India. Although it should receive more attention, severe anemia is one of the comorbidities that increases mortality in children who are severely undernourished. In SAM children, the liver function test (LFT), kidney function test (KFT), and complete blood count (CBC) are deranged, but their correlation with the prognosis is not well defined. The aim was to describe the anthropometric assessment and biochemical profile of children with SAM. Methods: This cross-sectional cohort study was performed at the Departments of Paediatrics and Biochemistry at G.S.V.M. Medical College, Kanpur, and at the Department of Biotechnology at Amity University Rajasthan, Jaipur. One hundred and six patients with SAM were enrolled; 53 were grouped as complicated SAM (Group 1) (dehydration and severe dehydration) and 53 were diagnosed as non-complicated SAM (Group 2). Results: Group II had significantly higher mean values for height, weight, mid-upper arm circumference (MUAC), head circumference, and body mass index (BMI) for age percentile compared to Group I, with P-values of 0.001. Group I had a significantly lower level of hemoglobin (8.86 g/dL ± 2.21 g/dL) compared to Group II (10.0 g/dL ± 1.83 g/dL) with a P-value of 0.003. The difference in the frequency of anemia between the groups was statistically significant, with a P-value of 0.026. Anemia significantly increased the risk of complicated SAM with an odds ratio of 2.60 [95% confidence interval (CI), 1.07-6.31, P = 0.001]. Conclusions: This study suggests that there may be a significant relationship between anemia and the development of complications in high-risk children with SAM.